2023
DOI: 10.3390/s23167256
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Android Malware in the Internet of Things through the K-Nearest Neighbor Algorithm

Himanshi Babbar,
Shalli Rani,
Dipak Kumar Sah
et al.

Abstract: Predicting attacks in Android malware devices using machine learning for recommender systems-based IoT can be a challenging task. However, it is possible to use various machine-learning techniques to achieve this goal. An internet-based framework is used to predict and recommend Android malware on IoT devices. As the prevalence of Android devices grows, the malware creates new viruses on a regular basis, posing a threat to the central system’s security and the privacy of the users. The suggested system uses st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Real-time detection, particularly in streaming environments, is becoming imperative to swiftly identify and counteract malware propagation. As the volume of malware samples and feature spaces continues to expand, scalability concerns must be addressed [44,[86][87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Open Challengesmentioning
confidence: 99%
“…Real-time detection, particularly in streaming environments, is becoming imperative to swiftly identify and counteract malware propagation. As the volume of malware samples and feature spaces continues to expand, scalability concerns must be addressed [44,[86][87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Open Challengesmentioning
confidence: 99%
“…Relevant research has been actively conducted on malware analysis (including malware detection [18,19], malware removal [20], and ransomware detection [21]) and binary code analysis [22,23]. However, anti-reversing techniques have not attracted special interest from researchers except for specific topics such as code virtualization [24,25].…”
Section: Related Workmentioning
confidence: 99%
“…Lee et al [11] proposed an anomaly detection model for aircraft using an SVM. Wang et al [12] demonstrated the performance of a naïve Bayesian-based [13] anomaly detection model for power plant fan systems by comparing the model with random forest (RF) [14] and k-nearest neighbor (KNN) models [15].…”
Section: Related Workmentioning
confidence: 99%
“…Normalization is applied to convert the data to the range of 0-1 for model training. Min-max scaling [42] is then applied, as shown in Equation (15). We divided the difference between X and X min by the difference between X max and X min , which yield X , i.e., the normalization result of X. X = (X − X min )/(X max − X min ) (15)…”
Section: Data Descriptionmentioning
confidence: 99%